THE EFFECT OF BENEFIT PERCEPTION AND BRAND TRUST ON GOJEK USER CUSTOMER SATISFACTION - Dewi Andriany; Anisah Fitri (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study was to determine the effect of perceived benefits and brand trust on customer satisfaction of GO-JEK users with a case study of UMSU students. The population is all UMSU students with a sampling technique, namely Accidental Sampling as many as 100 people, and the analysis technique used is quantitative analysis techniques, so the results of the study show that each variable perception of benefits and brand trust has a significant effect on customer satisfaction of GO-JEK users. UMSU students, namely the perception of benefits with a t value of 2.387 t table 1.984 with a significance of 0.000 0.05 and a brand trust value of 4.035 t table 1.984 with a significance of 0.000 .0.05 and simultaneously, the perceived benefits and brand trust variables have a significant effect on customer satisfaction of GO-JEK users by UMSU students with a value of Fcount 22,045Ftable 3,090. The perception of benefits and brand trust simultaneously (coefficient of determination) has an effect of 31.2% on customer satisfaction of GO-JEK users by UMSU students, while the remaining 68.8% is influenced by other factors not examined by this study.Keywords: Benefit Perception, Brand Trust and Customer Satisfaction